PERAN KECAMATAN BANTARGEBANG DALAM MENDUKUNG KETAHANAN PANGAN BERAS KOTA BEKASI - , MOCHTAR CAHYO UTOMO; , Prof. Dr. Ir. Edhi Martono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the condition of rice security in Kota Bekasi and Kecamatan Bantargebang, as well as knowing how big a role Kecamatan Bantargebang as district which has the largest paddy fields in the other districts. Methods of research using survey methods with descriptive qualitative approach and simple quantitative to obtained from secondary sources and primary data. Sources of information derived from the literature according to the problem and research objectives, in-depth interviews with several informants related to this research. The result showed that: food security of rice Kota Bekasi and Kecamatan Bantagebang not been met, this is due to the availability of rice production comes from internal sources, donations Kota Bekasi (1.05%) and Kecamatan Bantagebang (3.86%) is very small so that the dependence on external sources of rice production is very high (over 96%) and to external sources of rice production, the average donation Kota Bekasi (126.77%) and Kecamatan Bantagebang (36.43%). Meanwhile, for the aspects of distribution and access to and consumption of rice has been fulfilled. Kecamatan Bantargebang role as the largest districts with rice fields was not able to contribute much sufficient means for internal rice production in Kota Bekasi that only 0.13%, but in terms of population, Kecamatan Bantargebang contributed 4.15% to its population compared to the least with other districts, so that the rice needs of the residents of Kecamatan Bantargebang of 4.20% of the rice needs Kota Bekasi is not too large.